Clear cell and papillary renal cell carcinomas in hereditary papillary renal cell carcinoma (HPRCC) syndrome: a case report - Sophie Ferlicot; Pierre-Alexandre Just; Eva Compérat; Etienne Rouleau; Frédérique Tissier; Christophe Vaessen; Stéphane Richard (BMC, 2021)
Abstract Background Hereditary papillary renal cell carcinoma (HPRCC) is a rare autosomal dominant disease characterized by the development of multiple and bilateral papillary type I renal cell carcinomas (RCC) and papillary adenomas caused by activating mutations in the MET proto-oncogene. Classically, distinctive histological features of RCC are described according to the familial renal cell carcinoma syndrome. To date, no clear cell RCC has been reported in HPRCC syndrome. Case presentation We describe the case of a 51-year-old man with a germline MET mutation detected on peripheral blood testing, and no germline VHL mutation, who developed numerous papillary tumors but also unexpectedly clear cell renal cell carcinomas. During the follow-up, an adrenal metastasis was observed 7 years after the initial diagnosis corresponding to a clear cell RCC metastasis. By immunohistochemistry, clear cell tumors showed focal cytokeratin 7, moderate racemase, and diffuse and membranous CAIX expression, while papillary tumors expressed strong diffuse cytokeratin 7 and racemase without CAIX positivity. Using FISH, VHL deletion was observed in one of the clear cell tumors, and the metastatic clear cell tumor presented a trisomy of chromosomes 7 and 17. These last genomic alterations are usually detected in papillary RCC, highlighting the potential link between both histological subtypes of tumors and the HPRCC syndrome. Conclusions The pathologist must be aware that the presence of a non-papillary RCC associated with numerous papillary tumors should not exclude the diagnostic suspicion of HPRCC and thus to perform a thorough genomic study.